Anti-conspiracy attack threshold signature model and protocol. (5th September 2019) - Wang, Xiaoping; Ning, Zhenhu; Wang, Wei; Yang, Yongli
Threshold signature has security and robustness, so more and more scholars pay close attention to it. Aiming at the disadvantage that it cannot prevent conspiracy attack, this paper makes full use of tracing set and other technologies, proposes a threshold signature model which can withstand the conspiracy attack and resolves conspiracy attack problem successfully. Moreover, the model can prevent replay attack, has forward security and without the support of the trusted centre. At last, this paper proves that in the standard model, the model is unforgeable under adaptive chosen message attack.